Enhanced Bioavailability of Dihydrotanshinone I–Bovine Serum Albumin Nanoparticles for Stroke Therapy - Ren, Yanru; Feng, Yicheng; Xu, Kunyao; Yue, Saisai; Yang, Tiantian; Nie, Kaili; Xu, Man; Xu, Haijun; Xiong, Xin; Körte, Fabian; Barbeck, Mike; Zhang, Peisen; et al. (Frontiers in Pharmacology, 2021)
Dihydrotanshinone-I (DHT) is a natural component in Salvia miltiorrhiza and has been widely researched for its multiple bioactivities1,2,3,4. However, poor solubility and stability of DHT limits its desirable application for clinical purpures. Herein, DHT was encapsulated by bovine serum albumin (BSA) to enhance the bioavailability. Comparing to free DHT, DHT-BSA-NPs (NPs = nanoparticles) showed an improved solubility in Normal Saline (NS) and increased protection on hydrogen peroxide (H2O2)-induced oxidative damage in PC12 cells. In addition, DHT-BSA-NPs by intravenous injection (i.v) displayed a significant efficacy in the middle cerebral artery occlusion/reperfusion (MCAO) models，and without any impact on cerebral blood flow. In summary, DHT-BSA-NPs shows an enhanced bioavailability comparing with free DHT and a successful penetration into Central Nervous System for stroke therapy, demonstrating its application potential in cardio-cerebrovascular diseases.